Oligarchoz as a Successor of Postkolkhoz - Александр Михайлович Никулин (Journal of Economic Sociology, 2010)
The article is devoted to a new organizational form of a large private agricultural enterprise (or «oligarchozes») originated from post-Soviet collective-owned enterprises (kolkhozes). The ﬁ eldwork was conducted in several villages of Perm region in 2008. The author tries to  ﬁ nd answers on the following questions: where did «oligarchozes» come from? what relations are being formed between local rural communities, the state and new Russian rural oligarchs? what are major similarities and differences between old-type postkolkhozes and new «oligarchozes»?